2020
DOI: 10.4103/ccd.ccd_455_19
|View full text |Cite
|
Sign up to set email alerts
|

The tooth size discrepancy among orthodontic patients and normal occlusion individuals from Saudi Arabia: A three-dimensional scan analysis of diagnostic casts

Abstract: Background/Purpose: Tooth size discrepancy is one of the causative factors of malocclusion. This study aimed to establish the TDS among various malocclusion classes and normal occlusion subjects in a Southern Saudi population. Materials and Methods: The study casts of orthodontic patients from Southern Saudi Arabia (mean age: 19.6 years ± 2.45; n = 120) were randomly selected and grouped into eight equal classes based on Angle's classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…For the overall ratio, the study suggested a value of 92.51 ± 2.82, except for class III cases where the value was set at 91.97 ± 2.4 for females and 93.13 ± 2.6 for males ( 33 ). It was noted that most of the studies included in this systematic review had a relatively small sample size compared to this study where we evaluated 356 cases ( 34 – 37 ). However, the finding from the systematic review was not dissimilar from the results of this study, especially for the anterior ratio where both studies agreed on a value of 79%.…”
Section: Discussionmentioning
confidence: 96%
“…For the overall ratio, the study suggested a value of 92.51 ± 2.82, except for class III cases where the value was set at 91.97 ± 2.4 for females and 93.13 ± 2.6 for males ( 33 ). It was noted that most of the studies included in this systematic review had a relatively small sample size compared to this study where we evaluated 356 cases ( 34 – 37 ). However, the finding from the systematic review was not dissimilar from the results of this study, especially for the anterior ratio where both studies agreed on a value of 79%.…”
Section: Discussionmentioning
confidence: 96%
“…However, our study is in dispute with a study by Mulimani et al, [ 30 ] which found a significant correlation between malocclusion classes. However, Alshahrani found no significant difference in both ratios among the various malocclusion classes in Southern Saudi subjects [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Zilberman's study showed that OrthoCAD was an accurate alternative cast analysis software and therefore clinically acceptable for Bolton analyses 8 . Much of the historical literature that utilized Bolton's TSD also relied on physical study casts 9–12 . However, as the profession continues on its technological trajectory – becoming more deeply entrenched in a digital framework – it is conceivable to forecast a time that all orthodontic practices will utilize digital platforms offering more precise and personalized outcomes for patients.…”
Section: Introductionmentioning
confidence: 99%
“…8 Much of the historical literature that utilized Bolton's TSD also relied on physical study casts. [9][10][11][12] However, as the profession continues on its technological trajectory -becoming more deeply entrenched in a digital framework -it is conceivable to forecast a time that all orthodontic practices will utilize digital platforms offering more precise and personalized outcomes for patients. It follows that the orthodontic profession will likely evolve whereby studies are based solely on digital scans of teeth and the deployment of tooth measurement methods relying on digital technology that mirrors the contemporary diagnostic records used in most orthodontic practices today.…”
mentioning
confidence: 99%